Understanding gender in wheat-based livelihoods for enhanced WHEAT R4D impact in Afghanistan, Pakistan and Ethiopia - Drucza, Kristie (International Maize and Wheat Improvement Center, 2019)
Presented by Kristie Drucza (CIMMYT / WHEAT) on February 28, 2019, as part of the webinar 'Changing gender norms in agriculture projects - What works in Pakistan and Ethiopia'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on WHEAT.